Education, civic empowerment, and race: commentary on Meira Levinson’s No Citizen Left Behind - Hoskins, Zachary (2015)
Meira Levinson’s No Citizen Left Behind is a thoughtful, accessible, philosophically rich look at civic education in U.S. schools. The book’s central claims are, on the whole, quite persuasive. In the interests of fostering further discussion, this essay raises some questions about the book’s accounts of racial microaggressions in schools, the extent of authenticity in student experiences, and the practice of code-switching.